Zainichi Identity and American Ideology in Pachinko (2022): A Narratological Study of Literature Analysis - Khoirunnisa, Firda; Prabasmoro, Tisna; Adipurwawidjana, Ari Jogaiswara (Journal of Language and Literature Studies, 2025)
Pachinko (2022) is an American series produced and aired by Apple TV+ portraying generations of Zainichi trying to settle in Japan after their displacement from Japan-Occupied Korea that at the same time shows how American ideology as colonial contagion spread within the people. The act of mimicry displayed in the film’s narratology, production process, and additional intrinsic elements that differ from its novel version, Pachinko (2017), makes this series tend to become something ambivalent and lack a definite position—as if it gets recolonized after being free on its own. Other than that, dynamics during the Japanese occupation, whose practices are primarily inspired by the U.S., can be seen as setting the standard for ongoing life. By observing the series with film narratology including Verstraten’s (2009) mise en scene and focalization linked with theories surrounding the topic of postcolonialism, diaspora from forced migration, and the tendency to imitate or mimic, how the image of the U.S. wants to be built throughout the series can be identified. Moreover, focus on the theory of Bhabha’s (1994) mimicry will help to see how the production tries to make Zainichi seems to ‘put effort’ to be as similar as American. This series, as one of modern media platforms delivered into a private area, acts as the contagion transmitter with having the narrative form sick and infect the contagion within it towards the audience. With that, this research aims to analyze these forms of ‘contagion’ and the attempt at recolonization done by Americans which makes the contribution to the postcolonial discourse is to dissect this ‘new way’ of recolonization. Therefore, this research argues that forms of colonial contagion persist into the postcolonial era, perpetuated due to the obsession with gaining American recognition as a global center.